PENERAPAN PENDEKATAN SAINTIFIK OLEH GURU DALAM PEMBELAJARAN SOSIOLOGI KELAS XI SMAN 1 SENGAH TEMILA - Yanti, Natalia Desi; Salim, Izhar; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to describe the Application of Scientific Approach by Teacher in Sociology Learningin Class XI of SMAN 1 SengahTemila. This research aimed to determine the Application of the Scientific Approach and the obstacles in applying the scientific approach. The research method used was qualitative research with descriptive methods. Data collection techniques used was direct communication techniques through observation, interviews, and documentation, with data collection tools in the form of observation guides and interview guides. The results of his research were (1) Application of the Scientific Approach to Class XI of SMAN 1 SengahTemila in learning activities including five activities, namely observing, asking questions, gathering information, reasoning and communicating in the learning process it’s giving students an understanding in knowing and understanding various materials used in scientific approach. (2) The teacher’s obstacle in applying the scientific approach to Class XI of SMAN 1 SengahTemila namely it was difficult to develop the teaching materials because the lack of existing facilities at schools that made teacher and students unable to access material available on social media as additional teaching material for students. Keywords: Scientific Approach, Sociology Learning.